ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN MEMBAYAR PAJAK (Studi Kasus Pada Kantor Pelayanan Penyuluhan dan Konsultasi PerpajakanPasir Pengaraian) - Afrita Gusrina,; Nurhayati,; Sri Yunawati, (AKPEM : Jurnal Akuntansi Keuangan Dan Akuntansi Pemerintahan, 2021)
The purpose of this study was to determine: whether tax counseling, tax incentives, tax officer services and the implementation of tax sanctions affect the willingness to pay taxes either partially or simultaneously. This study uses primary data obtained from questionnaires and secondary data obtained from the Office of Tax Counseling and Consultation Services (KP2KP) Pasir Pengaraian. The method used is a quantitative method. Sampling was done by using Convenience Random Sampling technique. The analysis technique used is multiple linear regression analysis, then hypothesis testing using t test and using F test. The results of this study indicate that the tax counseling variable partially affects the willingness to pay taxes, the tax incentive variable does not partially affect the willingness to pay taxes, the tax officer service variable has a partial effect on the willingness to pay taxes, and the variable of the implementation of tax sanctions has no partial effect. partial to willingness to pay taxes. Simultaneously, tax counseling, tax incentives, tax officer services, implementation of tax sanctions affect the willingness to pay taxes.